Modeling the effects of rainfall intensity on speed-flow-density relationship at North Luzon Expressway (NLEX) - Mejia, Hanzel N.
The study was conducted to model and establish a relationship about the effects of rainfall intensities on key traffic stream parameters: average volume, average speed, free flow speed, capacity, critical density, and speed at capacity. Speed and volume data were gathered using loop detectors near Balintawak toll plaza in NLEX for a period of seven months from June to December 2016. Rainfall data were obtained from the nearest automatic weather station. Traffic data were segregated unto different rainfall conditions: clear (0 mm rainfall/hr.), light (0.1-2.5 mm rainfall/hr.), moderate (2.6-7.5 mm rainfall/hr.), and heavy (above 7.5 mm rainfall/hr.). Regression analysis were done for speed-density and flow-density relationships. Different models were considered in the calibration of the data. The exponential model by Underwood was elected because of its consistency in better fitting evidenced by higher coefficient of determination values (R2). Key traffic flows were computed under different rainfall conditions and results were compared. It was found out that different rainfall intensities have a significant effect on traffic flow. The reduction in average speeds are about 5.34 percent under light rain conditions, 6.3 percent under moderate rain Ave conditions, and 7.4 percent under heavy rain conditions. The average volume decreased by 2.92 percent, 10.62 percent, and 12.39 percent while the respective capacities reduced by 3.67 percent, 7.6 percent, and 17.44 percent under light, medium, and heavy rain conditions, respectively. Free flow speed and speed at capacity also decreased by 6.9-11.05 percent and 12.89-16.65 percent, respectively. Lastly, the jam density has no significant change under different rainfall conditions. The findings reveal that the effects of rainfall are significant to traffic flow at 95 percent level of confidence. Generalized prediction models for speed-density and flow-density relationships were also proposed and calibrated.